Improving Students' Ability to Solve National Midwifery Competency Test Questions Using Google Sites Learning Media - Kasmiati, Kasmiati Arif; Rasako, Hairudin; Fasiha, Fasiha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The D-III midwifery study program at the Maluku Health Polytechnic in 2021 has a passing percentage of >60% for First Takers. This study aims to determine the increase in students' ability to complete midwifery competency exam questions using Google sites learning media as a student step in facing midwifery competency exams. This study used the Quasy Experiment method with a pretest-posttest design, where a sample of 15 people was tested using the sample T-test to assess the increase in students' abilities before and after participating in learning. The results showed that there was an increase in students' abilities with a P-value of 0.00, an increase of 63%, which means that students' ability to answer midwifery competency exam questions increased. So that this media can be the best solution for students to prepare themselves early for midwifery competency exams.